2022
DOI: 10.1002/jemt.24243
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic visualization of the antibiofilm potential of essential oils against Staphylococcus aureus and Klebsiella pneumoniae

Abstract: Biofilms are known to pose great risks in clinical settings, drinking water systems, and food industries as they show considerable resistance to various environmental stresses. This study investigates the antibiofilm potential of different essential oils against the test organisms Staphylococcus aureus (ATCC 25923) and Klebsiella pneumoniae (ATCC 13883). Moreover, different stages of biofilm formation were also assessed using light microscopic assays. For determining the antibiofilm activity, a total of five e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Other studies have also showed significant antibacterial properties for cinnamon EO, which inhibited the growth of A. baumannii, P. aeruginosa and K. pneumoniae (El-Kattan and Allam, 2021;Ganicé t al., 2022;Coseriu et al, 2023). Furthermore, this EO exhibited higher antibiofilm activity against K. pneumoniae, followed by peppermint EO (Sarwar et al, 2022). Man et al ( 2019) investigated the antibacterial activity of some EO against some Gram-positive and Gram-negative bacteria, including K. pneumoniae strains.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also showed significant antibacterial properties for cinnamon EO, which inhibited the growth of A. baumannii, P. aeruginosa and K. pneumoniae (El-Kattan and Allam, 2021;Ganicé t al., 2022;Coseriu et al, 2023). Furthermore, this EO exhibited higher antibiofilm activity against K. pneumoniae, followed by peppermint EO (Sarwar et al, 2022). Man et al ( 2019) investigated the antibacterial activity of some EO against some Gram-positive and Gram-negative bacteria, including K. pneumoniae strains.…”
Section: Discussionmentioning
confidence: 99%
“…Although both dapsone and disulfiram have demonstrated some efficacy against resistant biofilm/persister forms of Borrelia burgdorferi [ 74 , 94 , 104 ], up to four different biofilm agents were regularly used during the DDDCT and HDDCT protocols to improve efficacy. These included Stevia [ 133 ], Biocidin [ 134 ], essential oils including oregano, cinnamon, and clove [ 135 ], as well as peppermint oil [ 136 ]. Rarely, a fifth biofilm agent, Ethylenediaminetetraacetic acid (EDTA) suppositories (Detoxamin, 750 mg) [ 137 ], was considered the last week of HDDCT if patients had extremely severe symptoms and/or had failed prior regimens with DDDCT and HDDCT, with or without bioactive silver hydrosol (Argentyn 23), which was used for its antibacterial and synergistic effects [ 138 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although both dapsone and disulfiram have demonstrated some efficacy against resistant biofilm/persister forms of Borrelia burgdorferi [71,118,119], up to four different biofilm agents were regularly used during the DDDCT and HDDCT protocols to improve efficacy. These included Stevia [120], Biocidin [121], essential oils, including oregano, cinnamon, and clove [122], and peppermint oil [123]. Rarely, a fifth biofilm agent, namely ethylenediaminetetraacetic acid (EDTA) suppositories (Detoxamin, 750 mg) [124], was considered in the last week of HDDCT if patients had extremely severe symptoms and/or had failed prior regimens with DDDCT and HDDCT, with or without bioactive silver hydrosol (Argentyn 23), which was used for its antibacterial and synergistic effects [125].…”
Section: Minimizing Potential Side Effects Of Dapsone Combination The...mentioning
confidence: 99%